Multimodal control of neck muscles for vestibular mediated head oscillation damping during walking: a pilot study - Hölzl, Matthias; Neuhuber, Winfried; Ueberschär, Olaf; Schleichardt, Axel; Stamm, Natalie; Arens, Christoph; Biesdorf, Andreas; Goessler, Ulrich; Hülse, Roland (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: It is still in question whether head oscillation damping during walking forms a part of the vestibular function. The anatomical pathway from the vestibular system to the neck muscles via the medial vestibulospinal tract (MVST) is well known but there is a lack of knowledge of the exact influence and modulation of each other in daily life activities. Methods: (I) We fixed a head–neck unit of a human cadaver specimen in a steal frame to determine the required pitch-torque for a horizontal head position. The mean value of the acquired pitch-torque was 0.54 Nm. (II) On a motorized treadmill we acquired kinematic data of the head, the sternum and both feet by wireless 3D IMUs for seven asymptomatic volunteers. Subsequently three randomized task conditions were performed. Condition 1 was walking without any irritation. Condition 2 imitated a sacculus irritation using a standardized cVEMP signal. The third condition used an electric neck muscle-irritation (TENS). The data were analyzed by the simulation environment software OpenSim 4.0. Results: 8 neck muscle pairs were identified. By performing three different conditions we observed some highly significant deviations of the neck muscle peak torques. Analysing Euler angles, we found during walking a LARP and RALP head pendulum, which also was strongly perturbated. Conclusion: Particularly the pitch-down head oscillation damping is the most challenging one for neck muscles, especially under biomechanical concerns. Mainly via MVST motor activity of neck muscles might be modulated by vestibular motor signals. Two simultaneous proprioceptor effects might optimize head oscillation damping. One might be a proprioceptive feedback loop to the vestibular nucleus. Another might trigger the cervicocollic reflex (CCR).
CRIS-Team Scopus Importer:2020-12-25
Keywords: Cervical vestibular-evoked myogenic potential (cVEMP); Head stabilization; Medial vestibulospinal tract (MVST); Neck muscles; Vestibulocollic reflex (VCR)/cervicocollic reflex (CCR)